An investigation of application developer’s awareness and attitude towards open government data in Malaysia - Wu, Tong; Mohd Mahdzir, Akbariah (International Journal of Engineering and Technology, 2019)
Governments across the globe are publishing official datasets and making it readily available online as open government data (OGD). Leaders of the OGD movement sought to engage developers to make information available not only for greater transparency and accountability but also incorporate it into applications, services and business developed to serve the public and foster social and economic growth. Given rising concerns over the OGD movement, Malaysia also navigates new frontiers of this digital revolution and embrace openness as part of the public effort across government sectors. However, much more efforts need to be done in order to help translate the data openness into practical results. In this regard, this paper briefly reviews the content of the Malaysia government data portal and conducted a preliminary survey gathered from various application developers aim to investigate the level of awareness and attitude based on their perceptions towards OGD in Malaysia. Presently, the results indicate that OGD in Malaysia is still scattered and the awareness among developers is still slim. Many developers are still reluctant and uncertain concerning the pursuit of OGD in their current projects. These findings argue that the potential of OGD is real, but it requires more positive promotion and improvement to enhance the level of awareness and civic consciousness so that successful application would take off in the future.Â Â